Use of intrawound vancomycin powder against postoperative infection after spine surgery - Takahashi, Hiroshi (Spine Surg Relat Res, 2018)
Local application of vancomycin has recently become widely used in spine surgery. However, local application is not included in the indication and has not been approved by the US Food and Drug Administration (FDA). Thus, we searched for reports with “intra wound-vancomycin” and “SSI” as keywords in the MEDLINE database, and investigated the efficacy, problems with use, and future prospects based on these reports. Intrawound vancomycin was described as effective in most of the reports, but was found to have no effect or to aggravate the condition in some reports. A toxic effect on osteoblasts due to a high local concentration was described in some reports, whereas local application was found to be safe in other studies. The amount of vancomycin used and the administration method varied among the reports. Overall, the results suggest that intrawound vancomycin is clinically effective, but this has yet to be established in a randomized controlled trial. There is a need to identify cases that should be selected for this treatment and to investigate the dose and optimum concentration of vancomycin for clinical use.